Cognitive development in childhood and drinking behaviour over two decades in adulthood. Issue 6 (13th May 2008) - Jefferis, B J M H; Manor, O; Power, C
Abstract : Background/aims: Childhood cognition predicts adult morbidity and mortality, potentially working through health behaviours. This study investigates if childhood cognition influences life course (i) non-drinking and (ii) binge drinking and pathways through which this might act—namely, childhood behaviour problems, adult social position and educational qualifications. Methods: Prospective cohort of British births in March 1958, with information on cognition at 7, 11 and 16 years and alcohol use at 23, 33 and 42 years. Non-drinkers drank "infrequently/on special occasions" or "never". Binge drinkers consumed ⩾10 units/occasion (men) and ⩾7 units/occasion (women). Results: Lower cognitive ability increased the odds of non-drinking at each adult survey (for example, for men at 42 years OR 1.52 (95% CI 1.34 to 1.72) per SD decrease in 7-year maths). Associations remained after adjustment for pathway factors (i) behaviour problems, (ii) adult social position and (iii) educational qualifications. Decreased ability rank across childhood (7–16 years) also increased odds of non-drinking at 42 years, but the association operated via pathway factors. Lower 7-year ability elevated the odds of 42-year binge drinking, operating via pathway factors. Declining ability rank across childhood also increased the odds of adult binge drinking; associations operated through behavioural problems, adult social position and qualifications. In women, the decline in risk of binge drinking from an age 23-year peak to 42 years was associated with higher 7-year score. Conclusions: Poorer childhood cognition was associated with non-drinking and binge drinking up to the early 40s. Associations between childhood cognition and drinking status may mediate between childhood cognition and adult health.